A Prototype-Based Resonance Model of Rhythm Categorization. (October 2014) - Bååth, Rasmus; Lagerstedt, Erik; Gärdenfors, Peter
Categorization of rhythmic patterns is prevalent in musical practice, an example of this being the transcription of (possibly not strictly metrical) music into musical notation. In this article we implement a dynamical systems' model of rhythm categorization based on the resonance theory of rhythm perception developed by Large(2010). This model is used to simulate the categorical choices of participants in two experiments of Desain and Honing(2003). The model accurately replicates the experimental data. Our results support resonance theory as a viable model of rhythm perception and show that by viewing rhythm perception as a dynamical system it is possible to model central properties of rhythm categorization.